DC Motor Settings Using Zigler Nichols PID Tuning as an Interactive Learning Media - Yatipai, Maksi; Subairi; Dirgantara, Wahyu (ENERGY: JURNAL ILMIAH ILMU-ILMU TEKNIK, 2024)
DC Motor is a direct current that is often used in everyday life that uses speed regulation, the DC Motor rotation will be given a load so we test the Motor rotation value according to the weight of the motor load that is generated after the Motor is activated. To find out the motor rotation and the result ing value after being given a load, we are here using the Arduino Mega component as a microcontroller, the IBT 2 driver as a DCb motor speed controller that has been given a load, the encoder as a copy of the old motor rotation data to the new motor data, the potentiometer as a sensor to find out DC Motor rotation, LCD to display data that has been taken, Arduino Ide as Software. And the control used is PID (proportional integral differential). This PID control system works by processing calculations based on the control variables Kp, Ki, and Kd to achieve conditions according to the expected setpoint.